TAPER MODELS FOR Pinus taeda L. BASED ON FORM CHANGE POINTS - de Souza, Carlos Alberto Martinelli (2016)
This work was planned to describe the change point of stem taper (pmf), the number of geometric change points, adjust and compare mathematical models to predict diameters along of stem of Pinus taeda L. The data sampled were measured on trees growing in stands implanted with spacement of 2,50 x 2,50m, thinned at 9 and 14 years and final cut at 30 years old, from Klabin S.A., Telêmaco Borba, Paraná state, Brazil. Fourty trees between the average and dominant trees were cut and measured with Smalian method  at the positions 0,10m; 0,30m; 0,80m; 1,30m; and from them at each 1m to the top. At crown part the measured point were moved among knot. After that, at each measured point, slices to stem analysis were cut. If considered the age, a group of 649 trees between 8 to 30 years old resulted of the analysis. From this group, 50 trees were selected at random of each pmf class to modeling. The trees were grouped in pmf  by the number of change point of stem shape defined by the second derivative of the polynomial 5th. Degree 5th grad Polinon adjusted for each tree. The statistics of adjustment and precision, residuals graphics, bias (v), average difference (md), and difference of standard deviation (dpd) showed as better model the polynomial 5th. degree to predict the diameter at relative height of stem, and alternatively the Garay model and the Max-Burkhart with two segments or modify to one segment according to the number of  pmf calculated by the derivative.